Soliton pulse induces TPA effect in a silicon MRR all-optical switch - Nawi, I. N. M. (Institute of Electrical and Electronics Engineers Inc., 2016)
One of the critical problems in achieving a real practical all-optical switching devices is the requirement for a strong material nonlinearity. A strong material nonlinearity is crucial in order to achieve a low switching power. However, silicon-based all-optical switches require extremely high switching power due to its relatively weak nonlinear optical properties. To overcome this limitation, we have designed an all-optical switch configuration based on silicon microring resonator structure and demonstrated the switching operation based on the nonlinear effects induced by a soliton pulse. The soliton pulse induces free-carrier concentration through two-photon absorption (TPA) effect and this leads to enhance the refractive index change and enhance the nonlinearity of the silicon. Thus, the silicon microring resonator alters the nonlinear phase shift which is required for switching.